Biomass-based hard carbon negative electrode material, preparation method thereof and sodium ion battery
Through low-temperature cross-linking and high-temperature carbonization treatment of biomass and inorganic acids, a closed-cell structure hard carbon negative electrode material is generated, which solves the problem of low sodium storage capacity of biomass-based carbon materials and achieves efficient sodium ion storage.
Patent Information
- Application Number
- CN202510070018.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing biomass-based carbon materials have low sodium storage capacity in sodium ion batteries, which limits their application.
By mixing biomass raw materials with inorganic acids and cross-linking at low temperatures, a rich pore structure is generated and converted into a closed-cell structure at high temperatures, thereby achieving efficient storage of sodium ions.
The sodium storage capacity and first-time Coulomb efficiency of biomass-based hard carbon anode material have been significantly improved, and the problem of low sodium storage capacity in the prior art has been solved.
Smart Images

Figure CN119873791A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a biomass-based hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Rapidly evolving technologies such as electronics and efficient electric vehicles require advanced energy storage systems with low cost, high energy density, and long cycle capability. Lithium-ion batteries (LIBs) dominate the energy storage field due to their high energy density and good cycling stability. However, limited lithium supply and uneven resource distribution are the main limiting factors for their application in large-scale grid storage. In contrast, sodium-ion batteries (SIBs), which have chemical properties comparable to those of lithium-ion batteries, are considered a promising energy storage option due to the low cost and wide availability of sodium resources. The research progress of electrode materials undoubtedly plays a vital role in the commercial development of SIBs.
[0003] The design and development of high-performance carbon-based materials are key to the commercialization of SIBs in the future. The performance of carbon-based negative electrode materials is closely related to the precursors. Biomass is considered to be a promising precursor for functional carbon materials due to its abundant reserves and low cost. However, the sodium storage capacity of carbon-based materials obtained by direct carbonization of biomass is not high enough, which limits its application in sodium-ion batteries. Summary of the invention
[0004] In order to solve the problem of low sodium storage capacity of biomass-based carbon materials in the prior art, the present invention provides a method for preparing a biomass-based hard carbon negative electrode material, which realizes low-temperature cross-linking pore formation through inorganic acid, and then converts the open pores into a closed-pore structure through high-temperature treatment, thereby realizing the storage of sodium clusters in the closed pores, greatly improving its sodium storage capacity, and solving the problem of low sodium storage capacity of biomass-based carbon materials in the prior art.
[0005] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a biomass-based hard carbon negative electrode material comprises the following steps: S1: mixing a biomass raw material with an inorganic acid to obtain a mixed raw material; S2: cross-linking the mixed raw material under an inert gas atmosphere at 600-800° C. to obtain a cross-linked raw material; S3: After washing the cross-linked raw material to neutrality, the raw material is subjected to high-temperature carbonization treatment at 1000-1600° C. in an inert gas atmosphere to obtain a biomass-based hard carbon negative electrode material.
[0006] Optionally, the biomass-based raw material is selected from at least one of cellulose, lignin, and humic acid.
[0007] Optionally, the particle size of the biomass-based raw material is 20-200 mesh.
[0008] Optionally, the inorganic acid is selected from at least one of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid and hydrofluoric acid.
[0009] Optionally, the inorganic acid is an inorganic acid solution; the concentration of the inorganic acid in the inorganic acid solution is 1-15 mol L -1 .
[0010] Optionally, the mass ratio of the biomass raw material to the inorganic acid is 1:(0.3~0.9).
[0011] Optionally, the heating rate during the cross-linking treatment in step S2 is 0.5-5°C min -1 .
[0012] Optionally, in step S3, the heating rate during the high temperature carbonization process is 0.5-5°C min -1 .
[0013] Another object of the present invention is to provide a biomass-based hard carbon negative electrode material, which is prepared by the method for preparing the biomass-based hard carbon negative electrode material as described above.
[0014] Another object of the present invention is to provide a sodium ion battery comprising the biomass-based hard carbon negative electrode material as described above.
[0015] The beneficial effects of the present invention are: The preparation method of the biomass-based hard carbon negative electrode material provided by the present invention adopts biomass as the carbon source. Compared with carbon sources such as resin, the carbon source of the present invention has the advantage of low cost; and the preparation process is simple and easy to scale up production; the present invention uniformly mixes acid and biomass so that the two produce a rich pore structure during a low-temperature cross-linking process, and converts it into a closed-pore structure during a high-temperature carbonization process, thereby realizing efficient storage of sodium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0017] Figure 1 is a SEM image of the biomass-based hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 2 is the XRD pattern of the biomass-based hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 3 is a Raman graph of the biomass-based hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 4 is a pore size distribution diagram of the biomass-based hard carbon negative electrode material prepared in Example 1 of the present invention; Figure 5 This is a charge and discharge curve diagram of the biomass-based hard carbon negative electrode material prepared in Example 1 of the present invention when used as the negative electrode of a sodium ion battery. DETAILED DESCRIPTION
[0019] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0020] Although direct carbonization of biomass can produce carbon materials with large interlayer spacing and rich pore structure, most of its pores are open, which is not only not conducive to sodium storage, but also easily leads to low initial efficiency.
[0021] In order to solve the problem that the sodium storage capacity of biomass-based carbon materials in the prior art is not high, the present invention provides a method for preparing a biomass-based hard carbon negative electrode material, which comprises the following steps: S1: mixing a biomass raw material with an inorganic acid to obtain a mixed raw material; Preferably, the biomass raw material and the inorganic acid are mixed and stirred, and then dried to obtain a mixed raw material, and the mixing time is preferably 1 to 8 hours; the drying process is: keeping warm at a temperature of 100 to 180° C. for 12 to 48 hours; S2: cross-linking the mixed raw material under an inert gas atmosphere at 600-800° C., preferably, the heat preservation time during the cross-linking treatment is 1-4 h, to obtain a cross-linked raw material; preferably, the inert gas is nitrogen or argon; In this step, the biomass material and the inorganic acid undergo a cross-linking reaction to generate a rich pore structure; specifically, in this step, the inorganic acid can promote or catalyze the hydrolysis, dehydration, and aromatization reactions of the biomass raw materials, cross-link with the biopolymer, and have a pore-forming effect; by introducing the inorganic acid, the biomass can be cross-linked at a lower temperature and have a higher activation efficiency, thereby generating a large number of pores; S3: After washing the cross-linked raw material to neutrality, the raw material is subjected to high-temperature carbonization treatment at 1000-1600°C in an inert gas atmosphere, preferably the carbonization treatment is kept at this temperature for 1-4 h to obtain a biomass-based hard carbon negative electrode material; the inert gas is preferably nitrogen or argon; Preferably, in this step, the cross-linked raw material is repeatedly washed with deionized water until it is neutral, and then subjected to high-temperature carbonization treatment after drying treatment. It is further preferred that the specific process of the water washing treatment is to wash, centrifuge, and wash multiple times until the solution is close to neutral; the drying process is to keep warm at a temperature of 60-90°C for 12-48 hours; In this step, a high-temperature carbonization process is used to transform the pore structure produced during the cross-linking process into a closed-pore structure, thereby facilitating efficient storage of sodium ions.
[0022] The preparation method of the biomass-based hard carbon negative electrode material provided by the present invention adopts biomass as the carbon source. Compared with carbon sources such as resin, the carbon source of the present invention has the advantage of low cost; and the preparation process is simple and easy to scale up production; the present invention uniformly mixes acid and biomass so that the two produce a rich pore structure during a low-temperature cross-linking process, and converts it into a closed-pore structure during a high-temperature carbonization process, thereby realizing efficient storage of sodium ions.
[0023] In order to ensure the sodium storage capacity, the present invention preferably uses biomass-based raw materials selected from at least one of cellulose, lignin, humic acid, and crop waste.
[0024] In order to ensure the effect of the cross-linking reaction, the present invention preferably crushes, ball-mills and sieves the biomass in sequence to obtain fine powder as the biomass raw material; and further preferably, the particle size of the biomass-based raw material is 20-200 mesh.
[0025] In the present invention, the inorganic acid is preferably selected from at least one of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, and hydrofluoric acid; further, the inorganic acid is preferably an inorganic acid solution; and the concentration of the inorganic acid in the inorganic acid solution is preferably 1 to 15 mol L -1 .
[0026] To ensure the cross-linking effect, the preferred mass ratio of the biomass raw material to the inorganic acid in step S1 of the present invention is 1:(0.3-0.9), that is, the mass ratio of the biomass raw material to the inorganic acid solution in step S1 is 1:(0.3-0.9).
[0027] The preferred heating process in step S2 and step S3 of the present invention is programmed heating, and the heating rate in the crosslinking treatment in step S2 and the high-temperature carbonization treatment in step S3 is preferably 0.5-5°C min -1 .
[0028] In summary, the present invention provides a method for constructing a closed-pore structure of a biomass sodium storage negative electrode. Specifically, biomass is used as a raw material, mixed evenly with an acid, dried, subjected to a low-temperature cross-linking treatment under a protective atmosphere, repeatedly washed to neutrality, and then carbonized at a high temperature to obtain a biomass-based negative electrode material. The number of hard carbon closed pores can be adjusted by changing the ratio of biomass to acid.
[0029] The core goal of the present invention is to solve the deficiencies in the biomass sodium storage negative electrode material technology, and proposes a new preparation process for constructing a closed-pore structure for biomass-based sodium storage negative electrodes. This method uses cross-linking technology to form pores, and converts open pores into closed-pore structures through high-temperature treatment, thereby realizing the storage of sodium clusters in closed pores and greatly improving its sodium storage capacity. Constructing a closed-pore structure in a carbon material can not only significantly improve its sodium storage capacity, but also improve its first coulombic efficiency through desolvation. The biomass carbon material obtained by this process has a higher sodium storage specific capacity and first coulombic efficiency, and the process is simple, the conditions are mild and the controllability is strong, which provides strong support for industrial promotion and application.
[0030] Another object of the present invention is to provide a biomass-based hard carbon negative electrode material, which is prepared by the method for preparing the biomass-based hard carbon negative electrode material as described above.
[0031] The biomass-based hard carbon negative electrode material provided by the present invention uses biomass as a carbon source during the preparation process. Compared with carbon sources such as resins, the carbon source of the present invention has the advantage of low cost; and the preparation process is simple and easy to scale up production; the present invention uniformly mixes acid and biomass so that the two produce a rich pore structure during a low-temperature cross-linking process, and converts it into a closed-pore structure during a high-temperature carbonization process, thereby achieving efficient storage of sodium ions.
[0032] Another object of the present invention is to provide a sodium ion battery comprising the biomass-based hard carbon negative electrode material as described above.
[0033] The sodium ion battery provided by the present invention adopts a biomass-based hard carbon negative electrode material. Biomass is used as a carbon source in the preparation process. Compared with carbon sources such as resins, the carbon source of the present invention has the advantage of low cost; and the preparation process is simple and easy to scale up production; the present invention uniformly mixes acid and biomass so that the two produce a rich pore structure during a low-temperature cross-linking process, and converts it into a closed-pore structure during a high-temperature carbonization process, thereby realizing efficient storage of sodium ions.
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0035] Example 1 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: The biomass lignin was crushed, ball-milled and sieved in sequence to obtain fine powder with a particle size of 200 meshes to obtain a biomass raw material; the biomass raw material was mixed with phosphoric acid at a mass ratio of 1:0.75, stirred for 8 hours, and dried at a temperature of 150°C for 12 hours to obtain a mixed raw material; the concentration of phosphoric acid was 14.7 mol L -1 ; S2: The mixed raw materials were heated at 5 °C min under a high-purity nitrogen atmosphere. -1 The temperature is raised to 600°C at a heating rate of 100°C and kept at this temperature for 2 hours to obtain a cross-linked raw material; S3: After the cross-linked raw materials were washed several times, centrifuged, washed to neutrality, and dried at 80 °C for 2 h, they were heated at 5 °C min in a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0036] The biomass-based hard carbon negative electrode material was tested, Figure 1 This is the SEM image of the biomass-based hard carbon negative electrode material. From the SEM image, it can be seen that the prepared carbon material is in irregular granular shape; Figure 2 is the XRD pattern of the biomass-based hard carbon negative electrode material; Figure 3 This is the Raman diagram of the biomass-based hard carbon negative electrode material, and the ID / IG value is 0.929; Figure 4 The pore size distribution diagram of the biomass-based hard carbon negative electrode material is shown in Figure 2. The pore volume is 0.18 m 3 g -1 .
[0037] Example 2 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: The biomass lignin was crushed, ball-milled and sieved in sequence to obtain fine powder with a particle size of 200 meshes to obtain a biomass raw material; the biomass raw material was mixed with phosphoric acid at a mass ratio of 1:0.3, stirred for 4 hours, and dried at a temperature of 100°C for 24 hours to obtain a mixed raw material; the concentration of phosphoric acid was 14.7 mol L -1 ; S2: The mixed raw materials were heated at 0.5 °C min under a high-purity nitrogen atmosphere. -1 The temperature is raised to 600°C at a heating rate of 100°C and kept at this temperature for 2 hours to obtain a cross-linked raw material; S3: After the cross-linked raw materials were washed several times, centrifuged, washed to neutrality, and dried at 80 °C for 2 h, they were heated at 0.5 °C min in a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0038] Example 3 This embodiment provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: The biomass lignin was crushed, ball-milled and sieved in sequence to obtain fine powder, the particle size of the fine powder was 200 mesh, and the biomass raw material was obtained; the biomass raw material was mixed with phosphoric acid at a mass ratio of 1:0.9, stirred for 8 hours, and dried at a temperature of 150°C for 12 hours to obtain a mixed raw material; the concentration of phosphoric acid was 14.7 mol L -1 ; S2: The mixed raw materials were heated at 2.5 °C min under a high-purity nitrogen atmosphere. -1 The temperature is raised to 600°C at a heating rate of 100°C and kept at this temperature for 2 hours to obtain a cross-linked raw material; S3: After the cross-linked raw materials were washed several times, centrifuged, washed to neutrality, and dried at 80 °C for 2 h, they were heated at 2.5 °C min in a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0039] Example 4 The difference between this embodiment and embodiment 1 is that step S2 is: In a high-purity nitrogen atmosphere, the -1 The temperature was raised to 800°C at a heating rate and kept at that temperature for 1 hour to obtain the cross-linked raw material.
[0040] Example 5 The difference between this embodiment and embodiment 1 is that step S3 is: The cross-linked raw materials were washed several times, centrifuged, washed to neutrality, and dried at 80 °C for 2 h. -1 The temperature was raised to 1600°C at a heating rate of 1.5°C and kept warm for 1 hour for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0041] Each comparative example in the present invention is used for comparison with Example 1.
[0042] Comparative Example 1 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: The biomass lignin is crushed, ball-milled and sieved in sequence to obtain fine powder, the particle size of the fine powder is 200 mesh, and the fine powder is dried at a temperature of 150°C for 12 h to obtain a biomass raw material; S2: The biomass raw material was heated at 5 °C min under a high-purity nitrogen atmosphere. -1 The temperature is raised to 600°C at a heating rate of 10000 °C and kept at this temperature for 2 hours to obtain the treated raw material; S3: After the treated raw materials are washed several times, centrifuged, washed to neutrality, and then dried at 80 °C for 2 h, they are heated at 5 °C min in a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0043] Comparative Example 2 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: The biomass lignin was crushed, ball-milled and sieved in sequence to obtain fine powder with a particle size of 200 meshes to obtain a biomass raw material; the biomass raw material was mixed with phosphoric acid at a mass ratio of 1:0.75, stirred for 8 hours, and dried at a temperature of 150°C for 12 hours to obtain a mixed raw material; the concentration of phosphoric acid was 14.7 mol L -1 ; S2: The mixed raw materials were heated at 5 °C min under a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0044] Comparative Example 3 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: The biomass lignin was crushed, ball-milled and sieved in sequence to obtain fine powder with a particle size of 200 meshes to obtain a biomass raw material; the biomass raw material was mixed with phosphoric acid at a mass ratio of 1:0.75, stirred for 8 hours, and dried at a temperature of 150°C for 12 hours to obtain a mixed raw material; the concentration of phosphoric acid was 14.7 mol L -1 ; S2: The mixed raw materials were heated at 5 °C min under a high-purity nitrogen atmosphere. -1 The temperature is raised to 300°C at a heating rate of 100°C and kept at this temperature for 2 hours to obtain a cross-linked raw material; S3: After the cross-linked raw materials were washed several times, centrifuged, washed to neutrality, and dried at 80 °C for 2 h, they were heated at 5 °C min in a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0045] Comparative Example 4 This comparative example provides a method for preparing a biomass-based hard carbon negative electrode material, comprising the following steps: S1: crushing, ball milling and sieving the biomass lignin in sequence to obtain fine powder, the particle size of the fine powder is 200 mesh, and the biomass raw material is obtained; the biomass raw material is mixed with oxalic acid in a mass ratio of 1:0.75, stirred for 8 hours, and dried at a temperature of 150°C for 12 hours to obtain a mixed raw material; S2: The mixed raw materials were heated at 5 °C min under a high-purity nitrogen atmosphere. -1 The temperature is raised to 600°C at a heating rate of 100°C and kept at this temperature for 2 hours to obtain a cross-linked raw material; S3: After the cross-linked raw materials were washed several times, centrifuged, washed to neutrality, and dried at 80 °C for 2 h, they were heated at 5 °C min in a high-purity argon atmosphere. -1 The temperature was raised to 1400°C at a heating rate of 300 °C and kept at this temperature for 3 h for high-temperature carbonization treatment to obtain a biomass-based hard carbon negative electrode material.
[0046] The sodium storage performance of the hard carbon negative electrode materials prepared in the embodiments of the present invention and the comparative examples was evaluated by button cells. The mass ratio of the electrode slurry was active material (hard carbon material): conductive agent (carbon black): binder (polyvinylidene fluoride) = 90:5:5. An appropriate amount of N-methylpyrrolidone was added to prepare a slurry, which was coated on a copper foil with a coating thickness of 100 μm. After drying and pressing, a pole piece was made. Metallic sodium was used as the counter electrode and 1 mol L -1 NeA 6 DEC+EC (volume ratio of 1:1) solution was used as electrolyte and glass fiber GF / C was used as separator to assemble 2032 button cells. -1 The charge and discharge performance was tested at a current density of , and the test results are shown in Table 1; Figure 5 The charge and discharge curve of the hard carbon negative electrode material prepared in Example 1 as the negative electrode of a sodium ion battery, with a reversible capacity of 446.6 mAh g -1 .
[0047] Table 1 It can be seen from the above table that the hard carbon negative electrode materials prepared in various embodiments of the present invention have higher sodium storage capacity and first coulombic efficiency.
[0048] The difference between Comparative Example 1 and Example 1 is that no inorganic acid is added; due to the lack of activation and cross-linking effect of the inorganic acid, only a small amount or no closed pores are generated during the carbonization process, and the sodium storage capacity and initial efficiency of the prepared hard carbon negative electrode material are relatively low.
[0049] The difference between Comparative Example 2 and Example 1 is that the mixed raw materials are not cross-linked at 600-800°C; because the inorganic acid and biomass can only undergo activation and cross-linking in a specific temperature range, high-temperature carbonization is directly performed. Although there is inorganic acid in the raw materials, the activation and cross-linking cannot be effectively carried out, and the prepared hard carbon negative electrode material has no closed pores, resulting in lower capacity and initial efficiency.
[0050] The difference between Comparative Example 3 and Example 1 is that the temperature of the cross-linking treatment in step S2 is changed to 300°C; since the activation and cross-linking effect of the inorganic acid is limited at this temperature, the prepared hard carbon negative electrode material has no closed pores, resulting in its low capacity and first efficiency.
[0051] The difference between Comparative Example 4 and Example 1 is that oxalic acid is used instead of phosphoric acid; because under the reaction conditions provided by the present invention, the effect of oxalic acid on pore formation by activation is very limited, the number of closed pores in the prepared hard carbon negative electrode material is small, resulting in low capacity and first efficiency.
[0052] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a biomass-based hard carbon negative electrode material, characterized in that: The steps include: S1: mixing a biomass raw material with an inorganic acid to obtain a mixed raw material; S2: cross-linking the mixed raw material under an inert gas atmosphere at 600-800° C. to obtain a cross-linked raw material; S3: After washing the cross-linked raw material to neutrality, the raw material is subjected to high-temperature carbonization treatment at 1000-1600° C. in an inert gas atmosphere to obtain a biomass-based hard carbon negative electrode material.
2. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The biomass-based raw material is selected from at least one of cellulose, lignin, and humic acid.
3. The method for preparing a biomass-based hard carbon negative electrode material according to claim 2, characterized in that: The particle size of the biomass-based raw material is 20-200 meshes.
4. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The inorganic acid is selected from at least one of hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid and hydrofluoric acid.
5. The method for preparing a biomass-based hard carbon negative electrode material according to claim 1, characterized in that: The inorganic acid is an inorganic acid solution; the concentration of the inorganic acid in the inorganic acid solution is 1 to 15 mol L -1 .
6. The method for preparing a biomass-based hard carbon negative electrode material according to any one of claims 1 to 5, characterized in that: The mass ratio of the biomass raw material to the inorganic acid is 1:(0.3-0.9).
7. The method for preparing a biomass-based hard carbon negative electrode material according to claim 6, characterized in that: The heating rate during the cross-linking treatment in step S2 is 0.5~5℃ min -1 .
8. The method for preparing a biomass-based hard carbon negative electrode material according to claim 6, characterized in that: The heating rate during the high temperature carbonization process in step S3 is 0.5~5℃ min -1 .
9. A biomass-based hard carbon negative electrode material, characterized in that: The method is used to prepare the biomass-based hard carbon negative electrode material according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: Comprising the biomass-based hard carbon negative electrode material as described in claim 9.
Citation Information
Patent Citations
Preparation method and application of biomass hard carbon for sodium ion battery negative electrode material
CN111847418A
Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material
CN113381016A
Preparation method of sodium ion battery negative electrode hard carbon material with closed microporous structure
CN117003237A
Lignin-based hard carbon material, preparation method thereof and application of lignin-based hard carbon material in sodium-ion battery
CN117902577A
Coal-based hard carbon as well as preparation method and application thereof
CN118004996A